Spatial strategic planning for optimal management of construction waste with recycling and reuse approach in Iran - Samaneh Javadifard; Fariborz Karimi (مهندسی و مدیریت ساخت, 2022)
Construction waste as a result of human construction activities on earth has caused many environmental problems. If the life cycle of the building, the three main stages of demolition, design and implementation are considered, each of them carries millions of tons of construction waste, but with strategic and strategic management, more control can be achieved over each one. It had steps, and minimized the amount of construction waste production, and it is also possible to define a spatial strategic plan for recycling and reuse of construction waste for more control and monitoring. Therefore, the current research seeks to investigate and describe the current situation, and provide an ideal perspective with regard to opportunities and threats, and in the next step, previous researches on the subject of construction waste management in the main phases of the project (demolition, design, implementation) review and spatial strategic plan of construction waste management is proposed in 15 components. In this research, information and data have been collected through library studies and analyzed.